Comparative Analysis of Professional Ethics in Legal Practice and Medical Practice - Yuliarpan, Pipit; Kurniati, Yeti; RAS, Hernawati (Formosa Journal of Social Sciences (FJSS), 2024)
This research investigates the comparison of professional ethics between legal practice and medical practice and how practitioners in both fields face ethical dilemmas and resolve moral conflicts. Through comparative analysis, we clarify the similarities and differences in the ethical codes and moral principles governing the practice of law and medicine and their implementation in practical situations. We found that both professions have a focus on individual interests, integrity, and fairness, although there are differences in the emphasis and application of these values. Legal practitioners and physicians face complex ethical dilemmas daily, and they rely on the guidance of ethical codes, moral principles, and consultation with colleagues or ethics committees to resolve moral conflicts that arise. Continued research could deepen understanding of the factors that influence ethical decision making and develop more effective strategies for dealing with moral challenges in the workplace